Factors Hindering the Economic Sustainability of Former Female Migrant Workers in Sumbawa Regency, Nusa Tenggara Barat Province - Ramlafatma, Ramlafatma; Oruh , Shermina; Kamaruddin , Syamsu A; Andi Agustang (Tinta Emas Institute, 2024)
This study provides an in-depth analysis of the factors that impede the economic sustainability of former female migrant workers in Sumbawa Regency. The research seeks to identify both cultural and structural barriers that hinder their economic stability, while proposing alternative solutions to enhance their economic resilience in line with the development goals of Sumbawa Regency. Utilizing a qualitative approach, the study identifies two primary categories of obstacles: cultural and structural. Cultural barriers include personal financial mismanagement, high familial dependency, and widespread fatalistic attitudes among former migrant workers. Structural barriers are primarily linked to exploitative practices by recruitment agents, such as unclear contracts, irresponsible conduct, agent-related debts, withheld wages, and a lack of accountability. These challenges are further exacerbated by limited government support, inadequate banking services, and restricted access to financial institutions. As potential solutions, the study proposes skills-based economic empowerment, improved access to capital, the development of social networks and community support, enhanced financial literacy and planning, and strengthened policy frameworks and legal protections.